SERUM EXPRESSION OF MICRORNA-142 IN A COHORT OF BULGARIAN PATIENTS WITH INFLAMMATORY BOWEL DISEASES - A. Atanassova (Trakia Journal of Sciences)
The study aims to assess the expression of serum miRNA-142_3p and miRNA-142_5p in IBD patients and its correlation with disease extent, activity and severity. It was performed on 35 patients with ulcerative colitis (UC), 35 patients with Crohn’s disease (CD) and 30 healthy controls. Serum miRNA142 expression was assessed using reverse transcriptase quantitative real time PCR (RT-qPCR), and then correlated with that of a group of 30 healthy subjects. It was also correlated with disease extent and disease activity and severity indices (CDAI, Montreal classification, Partial Mayo score). The patients’ group showed mean serum miR-142_3p expression of 2.69±1.96 for CD, 1.66±0.90 for UC and 1.25±0.91 for the control group and serum miR-142_5p expression of 2.42±2.08 for CD, 1.61±1.12 for UC and 1.21±0.78 for the control group with a significant difference between groups. Conclusion: The expression of miR-142_3p and miR-142_5p was significantly higher in patients with CD compared to patients with UC and the control group.